2021
DOI: 10.3390/conservation1010005
|View full text |Cite
|
Sign up to set email alerts
|

How Threatened Is Scincella huanrenensis? An Update on Threats and Trends

Abstract: It is important to understand the dynamics of population size to accurately assess threats and implement conservation activities when required. However, inaccurate estimates are harming both the threat estimation process, and the resulting conservation actions. Here, we address the extinction threats to Scincella huanrenensis, a species described in the People’s Republic of China, but also occurring on the Korean peninsula. Estimating the threats to the species is not an easy task due to its unknown population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, E. argus have small home ranges (Kim et al, 2012) and they are restricted to coastal sand dunes, inland grasslands along lakes, and mountain slopes with low vegetation cover (Lee et al, 2012). Finally, the distribution of the third species, S. huanrenensis, is poorly known although potentially distributed across a broader range than currently known (Shin et al, 2021), and the species is usually found in the forest interiors (Lee et al, 2012). The behavioral characteristics and habitat use of the three lizard species is likely the cause for the reduced risk of roadkill.…”
Section: Figurementioning
confidence: 99%
“…Similarly, E. argus have small home ranges (Kim et al, 2012) and they are restricted to coastal sand dunes, inland grasslands along lakes, and mountain slopes with low vegetation cover (Lee et al, 2012). Finally, the distribution of the third species, S. huanrenensis, is poorly known although potentially distributed across a broader range than currently known (Shin et al, 2021), and the species is usually found in the forest interiors (Lee et al, 2012). The behavioral characteristics and habitat use of the three lizard species is likely the cause for the reduced risk of roadkill.…”
Section: Figurementioning
confidence: 99%
“…We used MaxEnt for our modeling because of the algorithm's ability to explicitly account for spatial bias in the occurrence dataset (via a density raster; Shin, Messenger, et al, 2021). We calibrated the current habitat suitability model with 10,000 target group background points and 10-fold cross-validation (Thapa et al, 2018).…”
Section: Current Habitat Suitabilitymentioning
confidence: 99%